The Relationship Between the Network of Non-coding RNAs-Molecular Targets and N6-Methyladenosine Modification in Colorectal Cancer - Lu, Senxu; Ding, Xiangyu; Wang, Yuanhe; Hu, Xiaoyun; Sun, Tong; Wei, Minjie; Wang, Xiaobin; Wu, Huizhe (Frontiers in Cell and Developmental Biology, 2021)
Recent accumulating researches implicate that non-coding RNAs (ncRNAs) including microRNA (miRNA), circular RNA (circRNA), and long non-coding RNA (lncRNAs) play crucial roles in colorectal cancer (CRC) initiation and development. Notably, N6-methyladenosine (m6A) methylation, the critical posttranscriptional modulators, exerts various functions in ncRNA metabolism such as stability and degradation. However, the interaction regulation network among ncRNAs and the interplay with m6A-related regulators has not been well documented, particularly in CRC. Here, we summarize the interaction networks and sub-networks of ncRNAs in CRC based on a data-driven approach from the publications (IF > 6) in the last quinquennium (2016–2021). Further, we extend the regulatory pattern between the core m6A regulators and m6A-related ncRNAs in the context of CRC metastasis and progression. Thus, our review will highlight the clinical potential of ncRNAs and m6A modifiers as promising biomarkers and therapeutic targets for improving the diagnostic precision and treatment of CRC.